Herpesvirus Diseases in Humans and Animals: Recent Developments, Challenges, and Charting Future Paths - Šudomová, Miroslava; Hassan, Sherif T S (Pathogens (Basel, Switzerland), 2023)
Herpesviruses, a family of enveloped DNA viruses, pose significant threats to both humans and animals [...].